Phytochemical and biological screening of Lantana camara linn. leaves extract - Pandeya, Shiva; Sharma, Namrata; Basyal, Deepak (Journal of Nepal Chemical Society, 2022)
The current study evaluated the phytochemical and biological screening of Lantana camara (Verbenaceae). It is a highly invasive ornamental garden plant species, native to tropical and sub-tropical America. Leaves of L. camara were extracted successively by petroleum ether and methanol by continuous hot percolation. The phytochemical screening was carried out by color reaction with different reagents.  The Well diffusion method on Mueller Hinton agar was used for evaluating antimicrobial activity. The LD50 value was determined by acute toxicity studies. The analgesic activity was carried out by tail immersion method, antimotility activity was carried out by charcoal movement test and the antidiabetic activity was carried out by oral glucose tolerance test. The extractive value of methanolic and petroleum ether was found to be 10.11% and 3.11% respectively. The preliminary phytochemical screening showed a positive reaction test for glycoside, tannin, saponin, steroid, flavonoid, carbohydrates, diterpene, and triterpene. The extract showed significant antimicrobial activity against S. aureus (p